Impact of pre-pregnancy body mass index on the grading changes of Mallampati test during labor and delivery - Qufei CHEN; Yannan LI; Hua GAO; Huifen YIN (Zhongguo Linchuang Yixue)
ObjectiveTo explore the correlation between pre-pregnancy body mass index (BMI) and the risk of difficult airway during labor and delivery through grading changes of Mallampati test (MT). MethodsA total of 354 primiparous women who delivered at Obstetrics and Gynecology Hospital of Fudan University from October 2020 to April 2021 were enrolled and categorized into low BMI, normal BMI, and high BMI groups based on pre-pregnancy BMI. Changes in MT grading were analyzed during early labor, postpartum (20 minutes to 1 hour after placental delivery), and 48 hours postpartum. A multifactor logistic regression model was used to analyze the factors increased MT grading postpartum. ResultsAmong the 354 participants, 97 (27.4%) exhibited increased MT grading postpartum, with the proportion of women classified as MT grade 3-4 rising from 39 (11.0%) during early labor to 77 (21.8%) postpartum. By 48 hours postpartum, the number of women with MT grade 3-4 decreased to 21 (5.9%). Multifactor logistic regression analysis showed that low pre-pregnancy BMI (vs high BMI: OR＝2.15, 95%CI 1.02-4.53, P＝0.045) and snoring history during pregnancy (OR＝2.32, 95% CI 1.38-3.90, P＝0.001) were independent risk factors for postpartum MT grading elevation. ConclusionsMT grading might increase postpartum in parturients, with low pre-pregnancy BMI and prenatal snoring history identified as significant risk factors for elevated MT grading after delivery.